Hubungan self control dengan perilaku konsumtif belanja online pada mahasiswa rantau - Laura Putri Anggraini; Hudaniah, Hudaniah (Universitas Muhammadiyah Malang, 2023)
Abstract. Technological advances have brought changes in various aspects of life, including shopping. Various online shopping sites appear and make it easier for someone to make a purchase If migrate students do online shopping, if it is not accompanied by good self-control, it can give rise to consumerist behavior. If online shopping activities carried out by overseas students are not balanced with good self-control, it will lead to consumptive behavior. The purpose of this study was to find out whether there is a correlation between self-control and consumptive behavior in online shopping among overseas students. This study used a correlational quantitative approach with 358 respondents as subjects. Sampling was carried out using a purposive sampling technique with the criteria are overseas students who are studying outside the city, aged 18-24 years, and routinely shop online at least once a month. The instruments used in this research are the self-control scale and the consumptive behavior scale. Data analysis in this study used Spearman’s rank correlation. The results showed that there was a negative relationship between self-control and online shopping consumptive behavior among overseas students because p=-0,521 and p=0,000 < 0,05 was obtained. This shows that the higher the self-control of overseas students, the lower the consumptive behavior and otherwise. Keyword: Consumptive behavior, overseas student, self control